Can Collusion Promote Corporate Social Responsibility? Evidence from the Lab - Francisco Gomez Martinez; Sander Onderstal; Maarten-Pieter Schinkel (Tinbergen Institute, 2019)
Competition has been argued to erode socially responsible behavior in markets, suggesting that allowing cartel agreements among firms may promote public interest objectives. We test this idea in a laboratory experiment. Participants playing the role of firms choose between offering a Ôfair\~O and an Ôunfair\~O good to a consumer participant. When the unfair good is traded, a negative externality is imposed on a third party. We vary whether or not the firms are allowed to coordinate on the type of good they sell Ð while remaining in price competing. We find that the opportunity to coordinate leads to more coordinated equilibria, but has no significant impact on the fraction of fair goods traded on the market. Instead it polarizes: more of the same good, fair or unfair, is offered in coordination. Irrespective of whether quality coordination between firms is allowed, participants are more likely to trade the fair good, the stronger their third-party preferences are. These findings suggest that both consumer and managerial values are more important drivers of socially responsible behavior than opportunities for firms to coordinate their corporate social responsibility (CSR) activities. We highlight implications for competition policy, where cartels may be exempted on CSR grounds.
Keywords: L41; C92; M14; 330; Collusion; Corporate social responsibility; Public interest; Laboratory experiment; Competition policy